A fatal case of cerebral malaria complicated with Gemella bergeri bacteremia: Role of Plasmodium mitochondrial cox3 gene and MALDITOF mass spectrometry for species identification - Zainulabid, Ummu Afeera; Dian, Nor Diyana; Juma’at, Jauhary Effendy; Periyasamy, Petrick; Kori, Najma; Saw Kian, Cheah; Abdul Wahab, Asrul; Md Idris, Zulkarnain (2022)
Here, we described a fatal case of a 37-year-old returning traveller from Burkina Faso, West Africa, who presented with an acute fitting episode later diagnosed as cerebral malaria induced by Plasmodium falciparum based on microscopic examination and Plasmodium mitochondrial cytochrome c oxidase III (cox3) gene PCR target. Unfortunately, the patient passed away due to severe malaria with multiorgan failure complicated with Gemella bergeri bacteremia. G. bergeri was identified using MALDI-TOF mass spectrometry.